Colores en las personas, lugares y momentos: Una apuesta desde la Escuela Popular Colores para la Paz en la Montaña con Alma Viva a partir de la acción colectiva y educativa popular durante el año 2022 y el primer período del año 2023 (2023)
This degree work to obtain the title of Social Workers accounts for the community intervention project based on the methodology of the authors Barbero and Cortés (2005) in the Paraíso Mirador neighborhood The "Mountain with a Living Soul" with children from the territory with heterogeneous ages between 2 and 12 years, thanks to the articulation of the Violetta Community Library, El Mirador Public Library and the support of the Museum of the Self-constructed City, thanks to the formation of a team of Social Work students made up of María Alejandra Arango, Ana María Forero and Andrea Carolina Amado. This project is the result of the work of the different members and professionals of the Universidad Nacional de Colombia of the Escuela Popular Colores para la Paz: Catalina Guzman Fuentes, Laura Rivera Saavedra, Daniela Contreras Cortes, Stevan Cuaces Quistial, Estefany Caipa Giraldo and Juan Daniel Forero Mora. We find common ideas and interests to add transformation actions to the territory. In response to these joint desires, we created and continue to consolidate the Escuela Popular Colores para la Paz with the intention of approaching the issue of imperfect peace through personal peace from an alternative, critical and popular bet with children in the territory, taking into account its needs and the dynamism of the context itself, observing the normalization of violence as the main problem. These transformation actions are located from popular education, the insurgent paradigm, the epistemologies of the south proposed by the author Santos (2009) together with four monocultures and ecologies, transversal elements such as art and play. As a result of the process, we observe the creation of concepts in the face of personal peace associated with people, places and moments, the creation of an itinerant gallery where the artistic creations of children account for the proposals for the construction of peace scenarios from the perspectives of children from the global south.